PERANCANGAN BASIS DATA PENDAPATAN CARGO DAN PENCATATAN DATA PELANGGAN MENGGUNAKAN VISUAL BASIC 6.0 PADA PT INTAN LUBUK PERTAMA - Ginanti, Maulidya Sahira; Evayani, Evayani (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The purpose of this reaseach is to determine how the income accounting information systems and customer data records that are running at PT Intan Lubuk Pertama. The company is still using manual systems to perform each transaction. This resulted in the company slow in presenting relevant information, so can not work effectively and optimally in serving the required reports. According to these problems, the authors are interested in doing research with the title "Designing Database cargo revenue and customer data records using Visual Basic 6.0 on PT Intan Lubuk Pertama".Data used in this study is qualitative data, using descriptive research method, further data collection techniques using field study consisted of interviews, observation, and literature were obtained directly from the company. This design tool uses Diagram Context, Data Flow Diagrams (DAD), Entity Relationship Diagram (ERD), and normalization. Then will proceed to the design database, input and output.Based on the results of the study authors found that 1) Procedures company's revenue system does not operate effectively. 2) Weakness of the documents used, recording transactions and reports generated revenue is still done manually. 3) The process of designing the produce information that is processed and used, shorten the time in the presentation as well as allow companies to calculate the revenue earned for each report the calculation of the company's revenue is generated automatically.KeywordsDesign, Accounting Information Systems, Revenue, Visual Basic 6.0